PEMANFAATAN “TUAK” SEBAGAI BAHAN DASAR PEMBUATAN HAND SANITIZER - Anastasia Natalia Badar; Bonavantura Nggarang; Patrisia Dirna; Krisdolista Ecin (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
The increasing number of COVID 19 casesin Indonesia,especially in Manggarai, has caused a lot of anxiety and fear. The people is continuously urged to comply with health protocols so as not to be exposed to this very dangerous virus. This includes washing hands frequently with soap and water and using hand sanitizer. This causes the demand for hand sanitizers in the market to increase so that these products are increasingly slow and even unable to meet all people's requests. Therefore, many people try to make their own hand sanitizer by referring to the procedures set by WHO using alcohol, glycerol, and hydrogen peroxide and aquadest, the concentration of which is not less than 70% in order to function effectively as an antiseptic, so raw materials are needed. alternative alcohol from natural ingredients that can be found in the surrounding environment. In Manggarai district, one type of traditional drink with a fairly high alcohol content is "Tuak". Therefore, the using of tuak as a basic ingredient for making hand sanitizers is a new breakthrough to overcome the scarcity of hand sanitizers. The process of making hand sanitizer made from tuak goes through three steps, namely the preparation of materials and tools, the manufacturing process and the packaging process. The results of this innovation product are named "wacalime" hand sanitizer which is packaged in spray bottles to make it more effective and efficient